The dangerous overthrow of legal languaje - Guerra Arteaga, Hugo (2018)
This paper deals with the relationships between Language and Legal Science. The first part explores the incongruities of the post-Thruth; the second part recalls that the Law must be claimed as an expression of Legal Science. Then the fundamental links between language and juridicity are demonstrated, concluding that this relationship is not only instrumental, but a foundation of substantive Law in itself. Along these lines, we propose a reading of reality in times of postmodernity and the danger of the tendency to overturn the semantics and etymology of crucial terms such as revolution, terrorism and gender ideology, undermining the foundations of Law, which constitutes a threat in the search for the supreme ends of this discipline with respect to the order and the harmonious and peaceful structuring of the society and the empire of effective justice and the metaphysical justification. The conclusion offers an alternative control from the Legal Moral.